Patterns in counselling services provided at Saudi Ministry of Health medication counselling clinics - Reasons for referrals and subjects discussed: A cross-sectional study - Salhia, Huda; Mutlaq, Alaa; Alshaiban, Abdulrahman; Alsaleh, Ahmad; Alzahrani, Rasha; Alshennawi, Mohammed (Saudi pharmaceutical journal, 2023)
Pharmacists provide medication counselling services to improve patient knowledge and their adherence to prescription instructions, and to achieve the best possible health-related outcomes. Our study aim was to describe the patterns of the reasons for referral to counselling and the subjects discussed between pharmacists and patients, and the possible associations related to the susceptible patient groups (chronic and elderly), in Saudi Ministry of Health (MOH) medication counselling clinics. This was a descriptive cross-sectional study. An electronic data collection form was developed to document details about the medication counselling services that were provided to patients. The form consisted of three main areas: (1) patient demographics and counselling services characteristics; (2) reasons for referrals to the medication counselling clinics; and (3) the subjects that were discussed between pharmacists and patients in the counselling session. A comparison was conducted between chronic and non-chronic, and elderly and non-elderly patients. From May 2020 to December 2021, a total of 36,672 counselling service sessions were provided to 28,998 patients. The greatest proportion of reasons for referrals to counselling was that patients had chronic diseases (50.84%), patients were added a new medication (33.69%) or patients received multiple medications (polypharmacy) (22.71%). The most frequent subject discussed during counselling was general knowledge about medication (85.62%), the duration of therapy (68.42%) and the action that patients should take if they missed a dose of their medication (44.51%). Patients with chronic diseases showed a significantly greater frequency of referral to counselling compared to patients without chronic disease, due to polypharmacy, medication use during Ramadhan, adverse drug reactions (ADRs), dosing/interactions, high-alert medication and suspected nonadherence (P < 0.001). This led to a significantly greater frequency of discussions with patients with chronic conditions about their general medication knowledge, the duration of their therapy, missed doses, ADRs, medication reconciliation and medication use during Ramadhan (P < 0.001). Elderly patients recorded significantly more referrals to counselling related to chronic diseases and polypharmacy than their younger counterparts (P < 0.001); however, there was no significant difference between the elderly and non-elderly in the patterns of subjects discussed that were related to polypharmacy and chronic disease consequences. A significant spike was also reported in the frequency of delivery of counselling services to caregivers for the elderly (P < 0.001). The current state of medication counselling services in Saudi MOH facilities indicates that chronic disease and polypharmacy are the most significant reasons for referral to counselling, and that the subjects discussed the most during counselling are general knowledge about medication, duration of therapy and missed doses. Patients with chronic diseases have a higher frequency of referral to counselling and discussion about polypharmacy and its consequences than those without chronic conditions. Elderly patients also show a high frequency of referral to counselling about chronic diseases and polypharmacy. Caregivers of elderly patients require more education to maximise counselling effectiveness as they attend the majority of elderly patient counselling sessions.